Deixis Analysis On Richard Wright's Black Boy - An'imah, Lailati, Dr. Phil. Dewi Candraningrum, M.Ed, Dra. Malikatul Laila, M.Hum (2015)
The objectives of the study are to find out the type of deixis, and clarify the meaning of deixis used in Deixis Analysis on Richard Wright's Black boy. In collecting the data, the writer uses observation and documentation method by techniques of reading, selecting, identifying, and noting the deixis forms which can be found in Richard Wright's Black Boy's novel. This research employs the theory of deixis in discourse analysis, and the kinds of context for discourse analysis to clarify the meaning of deixis. The result of the study shows that, there are five deixis type found in the data: (1) Person deixis that is divided into first person deixis, second person, and third person; (2) Place deixis; (3) Time deixis; (4) Discourse deixis; and (5) Social deixis that is divided into absolute social deixis and relational social deixis. In clarifying the meaning of deixis, the researcher uses theory of contextual meaning. The researcher finds five deixis in the novel of Richard's Wright's Black Boy, The meaning of Person Deixis, First Person deixis the word (I) refers to Richard, Richard's mother, Richard's father; Richard's brother, one of gangs boys, Aunt Jody, Richard's friend, Mr. Burhan, Uncle Clark, Richard's teacher, a black man, Granny, editor, the Boss's son, Griggs, a white man, Mr. Crane, Reynold, Mrs. Moss, Bess, a catholic's man and a librarian. (2) Second person deixis the word (you) refers to Richard, Richard's mother, boy, Griggs, Bess, Catholic's man, Richard's father. The word (We) refers to Richard and his brother, Richard and his mother, Aunt Maggie and Granny, editor's company, Niggers, and Richard and Bess. (3) Third Person Deixis (He) refers to Father, Richard's brother, Doctor, Uncle Clark, the boy, Mr. Burder's son, Mr. Burder, Rebellious boy, editor, White Klu Kluxers, Granpa, Bess, uncle Tom, White Buyer, and Mr. Falk . The word (She) refers to Mother, Mama, Richard's Granny, Ma'am, Aunt Auddies, Mrs. Moss, Bess. The word (They) refers to some boys, gang of boys, Uncle Clark and Aunt Jody, Granny and Aunt Addies, White Klu Kluxers, and Richard's classmate. The meaning of Place Deixis, The word (Here) refers to Richard's house, outside the house, Mr. Burden's room, Aunt Jody's house, in the street of gang black man, and Mr. Pease's office. The word (Come) refers to the place where Richard burn the kitten, Granny's house, Aunt Jody, white man's office, Mr. Crane's office, doorway and in the window. The word (There) refers to kitchen, and outside the house. The word (Go) refers to Broad, in the kitchen, store, and bedroom. The meaning of Time Deixis, The word (now) refers to time when Papa can sleep after Richard killed the kitten, Time when boy was angry with Richard and time when Richard could read his paper, time when Richard getting a job, time when Bess orders Richard to receive her love, time when Mr. Crane asked Richard keep control if he wants to get a job, time when librarian asked Richard about the book, time when Richard felt that Bess is crazy and time when Richard different feeling after read some book in library. The word (This Night) refers to time when the mother giving teaching of life to Richard, time when Richard got punishment from Granny. The word (This Morning) refers to the time when Richard feels a naïve boy after meeting a girl like Bess. The word (One evening) refers to the time when mother asked Richard to go shopping for food, time when Richard and his brother were ordered to stay in their Uncle. The word (Tomorrow) refers to the time when Richard thinks that how to make her mother better, time when Richard got oppourtunity to read his paper. The meaning of Discourse Deixis, The word (This) refers to the preceding statement that is uttered by Richard to go out from the house, preceding statement from Richard after getting a test in his job. The word (That) refers to preceding statement that is uttered by white man to Richard to leave the south preceding statement that is uttered by white man to Richard to not use the language like white people in the office. The meaning of Social Deixis, The word (Mrs. Burder) refers to the Boss's of Richard mother, The word (Mr. Crane) refers to Richard's Boss, The word (Mr. Reynold) refers to white man in Richard's office, The word (Mrs. Moss) refers to Mother's Bess. The word (Mother) refers to Richard's mother, The word (Uncle Clark), (Uncle Tom), (Aunt Jody), (Aunt Maggie), (Aunt Addie) refers to Richard's Uncle and Richard's Aunt